An experimental investigation of a diesel engine using carbon nanotubes blended with biodiesel - Alenezi, R. A.; Norkhizan, A. M.; Rani, H. A.; Maulana, M. I.; Yasar, M. (IOP Publishing, 2019)
The implementation of nano-particles in various application tremendously rise due to its unique characteristics in enhancing the effectiveness of final products. The main purpose of this study is to investigate the effects of adding 50, 100 and 150 ppm carbon nanotubes in biodiesel blend (B10) on the performance, combustion characteristics and emissions of single cylinder diesel engine. The experiment was conducted on Yanmar Model TF120M diesel engine under constant engine speed of 1800 rpm and low, medium and full engine loads. The performances of the engine were analysed in terms of indicated power, fuel consumption, indicate specific fuel consumption and indicated mean effective pressure. While, in-cylinder pressure, in-cylinder temperature and combustion duration were analysed to investigate the combustion behaviour of fuel blends. From the study, addition of carbon nanotubes in biodiesel blends did improved the performances of engine, which reduce the indicated specific fuel consumption especially during low load condition. The peak in-cylinder pressure for CNTs fuel blends were higher than conventional diesel fuels (D100) in all load conditions. However, the in-cylinder pressure for B10C100 was slightly comparable with D100 during 14 Nm load condition.